1st November: All Saint’s Day - Sheveland, John N. (The expository times, 2015)
The article presents a sermon by John N. Sheveland of Gonzaga University in Washington for All Saint's Day on November 1, 2015. Topics mentioned include the rhythm of the liturgical cycle and common human experience, the depth and scope of global death from injustice, and the response of Jesus Christ to Lazarus' death in the Gospel of John.